Evaluating the Implementation of Sharia in Aceh, Indonesia: (Examining the Qanun Jinayat in Bireuen Regency) - Manan, Abdul; Salasiyah, Cut Intan (SCAD Independent, 2021)
This paper critically studied the perspectives of people living in Aceh, particularly in Bireuen toward the implementation and enforcement of Sharia. This study was conducted by qualitative approaches as a phenomenological study to cope with every idea emerging toward the legalization, implementation, and enforcement of sharia. The data were gathered by open-ended interviews to ensure that each perspective adjacent to the sharia was portrayed clearly. The result indicated that problems existed upon the implementation: the problems of Sharia formalization, unrelated qanun, the position of Sharia authority, polemics of Sharia, and other pros-and-cons of the Sharia itself. Hence, the government, along with relating parties, had to reconsider the strategies and ways in implementing sharia as a legal law. The point here was to make the Acehnese people performed and obeyed Islamic tenets as their dignities as Muslims, not by force or fear of penalties from the government.